Effects of folic acid on epithelial apoptosis and expression of Bcl-2 and p53 in premalignant gastric lesions - Cao, Da-Zhong (World J Gastroenterol, 2005)
AIM: To evaluate the effects of folic acid on epithelial apoptosis and expression of Bcl-2 and p53 in the tissues of premalignant gastric lesions. METHODS: Thirty-eight patients, with premalignant gastric lesions including 18 colonic-type intestinal metaplasia (IM) and 20 mild or moderate dysplasia, were randomly divided into a treatment group (n = 19) receiving folic acid 10 mg thrice daily and a control group (n = 19) receiving sucralfate 1000 mg thrice daily for 3 mo. All patients underwent endoscopies and four biopsies were taken prior to treatment and repeated after concluding therapy. Folate concentrations in gastric mucosa were measured with chemiluminescent enzyme immunoassay. Epithelial apoptosis and the expression of Bcl-2 and p53 protein in gastric mucosa were detected with flow cytometric assay. RESULTS: The mean of folate concentration in gastric mucosa was 9.03±3.37 μg/g wet wt in the folic acid treatment group, which was significantly higher than 6.83±3.02 μg/g wet wt in the control group. Both the epithelial apoptosis rate and the tumor suppressor p53 expression in gastric mucosa significantly increased after folic acid treatment. In contrast, the expression of Bcl-2 oncogene protein decreased after folic acid therapy. CONCLUSION: These data indicate that folic acid may play an important role in the chemoprevention of gastric carcinogenesis by enhancing gastric epithelial apoptosis in the patients with premalignant lesions.